Chemical and structural evolution of nano-oxides from mechanical alloying to consolidated ferritic oxide dispersion strengthened steel. (July 2022) - Spartacus, Gabriel; Malaplate, Joël; De Geuser, Frédéric; Mouton, Isabelle; Sornin, Denis; Perez, Michel; Guillou, Raphaëlle; Arnal, Benoit; Rouesne, Elodie; Deschamps, Alexis
Abstract: Ferritic Oxides Dispersion Strengthened (ODS) steels are of great interest for nuclear fission and fusion power plants. The nano-oxides embedded into the matrix provide the main contribution to the ODS steel strength. Understanding of the precipitation mechanism of ODS steels is thus critical for optimizing the fabrication process,  involving Mechanical Alloying (MA) of Fe-14Cr, Y2 O3  and TiH2  powders. In this study, results from small-angle X-ray and neutron scattering, atom probe tomography and electron microscopy have been combined to investigate the nano-oxides evolution throughout the whole consolidation thermal treatment until 1100 °C. After MA clusters are observed, composed of Y,  O and Ti. During heating these clusters grow and new ones nucleate, together with a sequential enrichment in Ti (from as-MA to 700 °C) and Y (between 900 and 1100 °C). A small quantity of Al is also found in the nano-oxides between 700 and 1100 °C. At 1100 °C the nano-oxides are found to be mainly Y2 Ti2 O7  and subsequently progressively transform to Y2 TiO5  during isothermal holding. Nano-oxides display however an unchanged extremely low coarsening rate, demonstrating the outstanding stability of both Y2 Ti2 O7  and Y2 TiO5  at 1100 °C. Graphical abstract: Image, graphical abstract